2018
DOI: 10.1175/jamc-d-17-0116.1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Rainfall Duration Bias in Dynamical Downscaling and Its Related Synoptic Patterns in Summertime Asian Monsoon

Abstract: Dynamical downscaling (DDS) was conducted over Japan by using a regional atmospheric model with reanalysis data to investigate the rainfall duration bias over Kyushu, Japan, in July and August from 2006 to 2015. The model results showed that DDS had a positive rainfall duration bias over Kyushu and a dry bias over almost all of Kyushu, which were emphasized for extreme rainfall events. Investigated was the rainfall duration bias for heavy rainfall days, accompanied by synoptic-scale forcing, in which daily pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The correlation in W‐Kyushu (Figure c) is negative in the south of Kyushu, and the magnitude is lower than that in Figure d. These results are consistent with previous studies using the station data and the Radar/Raingauge‐Analyzed Precipitation product (Oki et al, ; Tamaki et al, ; Tsuguti & Kato, ). Figures and indicate that the impact of global warming on heavy precipitation depends on the synoptic patterns causing heavy precipitation most frequently in each region.…”
Section: Resultssupporting
confidence: 90%
“…The correlation in W‐Kyushu (Figure c) is negative in the south of Kyushu, and the magnitude is lower than that in Figure d. These results are consistent with previous studies using the station data and the Radar/Raingauge‐Analyzed Precipitation product (Oki et al, ; Tamaki et al, ; Tsuguti & Kato, ). Figures and indicate that the impact of global warming on heavy precipitation depends on the synoptic patterns causing heavy precipitation most frequently in each region.…”
Section: Resultssupporting
confidence: 90%
“…To clarify the effect of rainfall duration bias to runoff, we developed a new method to artificially extend rainfall duration while maintaining total rainfall. According to Tamaki et al (2018), the ratio of average rainfall duration between dynamical downscaling data and observed data was 1.41 at the Shimouke dam site (site a in Fig. 1) under strong monsoon patterns, and 1.28 at Iwase dam site (site f in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…However, it cannot correct a duration bias. Recently, Tamaki et al (2018) suggested that the DDS tended to prolong heavy rainfall events in Kyushu, and the extent of this duration bias was closely related to synoptic weather patterns such as a persistent Baiu rainband across the island and the passage of a typhoon along the island.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations